KUALITAS PRODUK, STORE ATMOSPHERE DAN SOSIAL MEDIA MARKETING TERHADAP KEPUASAN KONSUMEN PADA WARUNG BLAYAG SARI NADI TAMAN KOTA SINGARAJA - Sudarnaya, Ketut; Giriani, Putu Ayu (Jurnal Daya Saing, 2025)
This study aims to determine product quality, store atmosphere and social media marketing on consumer satisfaction at Warung Blayag Sari Nadi Taman Kota Singaraja. Data analysis techniques used in this study are validity test, reliability test, classical assumption test, multiple linear regression analysis, model feasibility test (Goodness Of Fit), hypothesis test using SPSS Version 21.0 for windows. The results of this study indicate that product quality has a positive and significant effect on consumer satisfaction at Warung Blayag Sari Nadi Taman Kota Singaraja, from this it can be concluded that the better the quality of the products sold to consumers, the more it will increase consumer satisfaction to continue buying blayag at Warung Blayag Sari Nadi Taman Kota Singaraja. Store atmosphere has a positive and significant effect on consumer satisfaction at Warung Blayag Sari Nadi Taman Kota Singaraja, from this it can be concluded that a good store atmosphere can attract consumers to come, from this it can increase consumer satisfaction to buy blayag at Warung Blayag Sari Nadi Taman Kota Singaraja. Social media marketing has a positive and significant effect on consumer satisfaction at Warung Blayag Sari Nadi Taman Kota Singaraja, from this it can be concluded that the better the marketing through social media, the more consumer satisfaction in buying products at Warung Blayag Sari Nadi Taman Kota Singaraja.